PELATIHAN PEMBUATAN SELAI BERBAHAN DASAR BUAH PEPAYA DI DESA MASDA MAKMUR KECAMATAN RAMBAH SAMO KABUPATEN ROKAN HULU - Yunita, Imelda; Wulandari, Aisyah Asrie; Febriana, Aulia; Kusyardi, Dwi; Rizki, Farehan; Darmawan, Genta; Ambarwati, Nabilla Prima; Sitio, Novita Angelina; Permana, Phinastika Rajawali; Siagian, Rini Nopika; Sitindaon, Sintia Maria Magdalena (Universitas Teknokrat Indonesia, 2024)
This service activity is the first step in an effort to build the economic independence of the people of Masda Makmur Village, Rambah Samo District, Rokan Hulu Regency, Riau Province. This activity is carried out by providing training to the community in making papaya jam by utilizing the potential of local resources. The purpose of the activity is to develop product potential from local papaya resources available in Masda Makmur Village by providing training in making papaya jam. This activity can increase the knowledge of women in Masda Makmur Village in processing papaya into jam as an effort to utilize local resources. This training method was carried out by presenting material and training on making papaya jam to Family Welfare Empowerment in Masda Makmur Village. The participants of this training were Family Welfare Empowerment in Masda Makmur Village, Rambah Samo District, Rokan Hulu Regency, Riau Province. This training is expected to enhance skills and create business opportunities for the Family Welfare Empowerment in Masda Makmur Village.Keywords: papaya, jam, Processing, Family Welfare Empowerment.